The Effect Of Mindfulness Training To Reduce Anxiety In Nurses Of General Hospital X Ciamis - Fauziah, Fajrin Siti; Widyana, Rahma (Jurnal Indonesia Sosial Sains, 2025)
The objective of this study was to determine the effect of mindfulness training on female nurses in reducing anxiety. This study had 10 research subjects who were divided into 2 groups, namely 5 subjects for the experimental group (KE) and 5 subjects for the control group (KK). The selection of subjects was carried out randomly. This study used a pre-test post-test control group design. This study used an anxiety scale, FFMQ scale, observation, and interview. Data analysis used Mann Whitney-U to see the difference in anxiety levels in KE and KK. Wilcoxon T-Test was used to see the difference in anxiety levels in KE and KK before and after being given mindfulness training. The results of the analysis showed a difference in anxiety levels in KE and KK with a Z value of -2.312 with a significance of 0.021 (p>0.05). The post-test anxiety score on KE was lower with an average value of 89.8, KK had an average value of 113. Further test results at follow-up in KE and KK showed a significant difference in anxiety levels with a Z value of -2.619 and a significance of 0.009 (p<0.05). The anxiety score at follow-up showed a lower level of anxiety in KE with a mean score of 68.8 while KK had a mean score of 114.4. The T-test showed that there was a difference in anxiety levels at the post-test and follow-up in KE after being given mindfulness training with KK who were not given the treatment. This finding shows that mindfulness training can reduce the anxiety level of female nurses in public hospitals.